Heritabilities, genetics, and phenotypic correlations between carcass and live animal traits in sheep - Menzies, C.; Hillman, M.; Wheat, J.D.; Mackintosh, D.L.; Merkel, R.A. (Kansas Agricultural Experiment Station, 2011)
This is a contributing project to the North Central-50 Regional Sheep Breeding Project. The Kansas State project was initiated in the spring of 1959 to determine relationships between various carcass measurements and live animal traits, to estimate heritability of these traits, and to determine how findings may be applied to selection and breeding of meat-type lambs.
Keywords: Sheep; Heritabilities; Genetics; Phenotypic; Carcass